Modelling, validation and parameter sensitivity of regenerative hydraulic-electric shock absorber. Issue 4 (5th October 2021) - Zhang, Min; Hu, Cheng; Gao, Jingwei; Zheng, Peng
Abstract : Purpose: Suspension is a significantly important component for automotive and railway vehicles. Regenerative hydraulic-electric shock absorbers (RHSA) have been proposed for the purpose of attenuating vibration of vehicle suspension, and also recover kinetic energy originated from vehicle vibration that is conventionally dissipated by hydraulic dampers. To advance the technology, the paper aims to present an RHSA system for heavy-duty and railway vehicles and create a dynamic modelling to discuss on the development process of RHSA model. Design/methodology/approach: First, the development of RHSA dynamic model can be resolved into three stage models (an ideal one, a second one with an added accumulator and a third one that considers both accumulator and system losses) to comprehensively evaluate the RHSA's characterisation. Second, a prototype is fabricated for testing and the results meet desired agreements between simulation and measurement. Finally, the study of key parameters is carried out to investigate the influences of hydraulic-cylinder size, hydraulic-motor displacement and accumulator pre-charged pressure on the RHSA system. Findings: The findings of sensitivity analysis indicate that the component design can satisfy the damping characteristics and power performance required for heavy-duty vehicle, freight wagon and typical passenger train. The results also show that reducing the losses is highly beneficial for saving suspension energy, improving system reliability and increasing power-conversion efficiency. Originality/value: The paper presents a more detailed method for the development and analysis of a RHSA. Compared with the typical shock absorbers, RHSA can also recover the vibration energy dissipated by suspension.